Peculiarities of cellular, humoral links of immunity and dynamics of immunoglobulins in community-acquired pneumonia in adults and their importance for diagnostics and prognosis of the disease - Bereznyakov, Vladyslav; Korzh, Oleksiy; Krasnokutskiy, Sergiy (ScienceRise: Medical Science, 2021)
The aim of our work was to study the characteristics of the immune status based on the analysis of the cellular, humoral links of immunity and dynamics of immunoglobulins in adults with community-acquired pneumonia (CAP), and their importance in the pathogenesis and prognosis of the disease. Materials and methods. The study was carried out in the period 2017-2020 on the basis of the therapeutic department of the Municipal non-profit enterprise “City Clinical Multidisciplinary Hospital № 25” of Kharkiv City Council. The study involved 20 adult patients with CAP aged 18 to 80 years (mean age 36.5±10.3). The control group consisted of 20 apparently healthy individuals (mean age 39.5±12.5). The study of the immune status of patients was carried out by determining the phagocytic index, the content of lymphocytes, CD3+, CD4+, CD8+, CD16+, CD20+ and the level of immunoglobulins of classes A, G, M in the dynamics of the disease: on the first and tenth days after hospitalization. Results. On the first day of hospitalization, there was a significant imbalance in phagocytosis, T- and B-links of immunity. On the tenth day of treatment, the phagocytic index, the number of CD3+, CD4+, CD8+, CD16+ and CD20+ increased. An increase in Ig M, a decrease in Ig A and Ig G were also noted. Thus, standard therapy for patients with CAP leads to its clinical and radiological resolution, but is not accompanied by the normalization of immunity parameters. Conclusions. The features of immune disorders in patients with CAP were revealed: pneumonia increases the imbalance in the cellular link of immunity, the level of CD3+ and CD4+ decreases, there is no dynamics of the relative amount of CD20+. There are no significant changes in the humoral link of the immune status. For the treatment of patients with CAP, in addition to standard pharmacotherapy, it is necessary to include drugs that stimulate the immune system